The Effectiveness Of Muroja'ah In Prayer On The Quality Of Memorization - Arifa, Lutvia Rahma; Ridwan, Ari Mohamad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2024)
This article presents research on the effectiveness of muroja'ah in prayer and its impact on the quality of Qur'anic memorization among memorizers in West Java, which is known as an important region in the development of hafidz through the SADESHA program. This study identifies the challenges faced by memorizers, especially those who have graduated from pesantren, in maintaining their memorization due to their busy schedules and lack of time for muroja'ah. Using a descriptive correlational approach with quantitative methods, this study involved statistical analysis to explore the relationship between muroja'ah in prayer and memorization quality. Data were collected through interviews and documentation, and analyzed using bivariate methods and various statistical tests. The results showed that muroja'ah in prayer has a significant influence on improving the quality of memorization in Pondok Tahfidz Generasi Rabbani Qur'ani, with a strong correlation between the two variables, thus providing a clear understanding of the importance of this practice in maintaining memorization of the Qur'an.